Influence of temperature, sunlight and wind on the mobilization of propylene glycol from airport de‐icers by rainfall - Exton, Benjamin; Hassard, Francis; Medina, Angel; Grabowski, Robert C. (Wiley, 2026)
Commercial anti‐icers and de‐icers (CADs) are essential for safe winter operation; yet, their mobilization remains poorly understood, limiting the ability of airport operators to optimize treatment processes, thus presenting a significant risk to freshwater ecosystems. This study investigated the impact of meteorological conditions and durations on CAD mobilization during rainfall. Two common commercial formulations were subjected to a range of controlled meteorological conditions, including temperature (+18°C, +5°C and −5°C), wind and sunlight, over 1 or 2 weeks, followed by simulated rainfall, where glycol in runoff was analysed by HPLC every minute. Exposure to sunlight and wind substantially decreased propylene glycol mobilization (6.9%–45.3% decrease). However, higher temperatures increased runoff concentrations of the anti‐icing fluid (31.6%–36.9% increase). There were significant differences in mobilization rates between commercial products (p < 0.045). Weathering duration had a minimal effect on mobilization. These results offer critical insights for airport operators in contaminant mobilization and treatment.
Keywords: 37 Earth Sciences; 3701 Atmospheric Sciences; 41 Environmental Sciences; Environmental Engineering; airport anti-icer; airport de-icer; artificial rainfall; mobilization; runoff; transport mechanisms; water quality